2009
DOI: 10.1295/polymj.pj2009106r
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Induced Microstructures in Micro- and Nano-Suspensions and Related Physical Properties

Abstract: Progress in electrorheology was reviewed for micro-and nano-suspensions. Characteristics required for the suspensions and related materials were shown. Some proposed models were discussed. Electrically induced microstructures, yielding, and related physical properties were also discussed in terms of theory and experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 98 publications
(150 reference statements)
0
9
0
Order By: Relevance
“…10. [260][261][262][263] Bishop and his coworkers, for example, considered conducting NPs in an insulating liquid in a DC field. The contact electrification of a single NP leads it to execute oscillatory motion between the two plates.…”
Section: B Effect Of Magnetic/electric Fieldsmentioning
confidence: 99%
“…10. [260][261][262][263] Bishop and his coworkers, for example, considered conducting NPs in an insulating liquid in a DC field. The contact electrification of a single NP leads it to execute oscillatory motion between the two plates.…”
Section: B Effect Of Magnetic/electric Fieldsmentioning
confidence: 99%
“…These studies showed that the attraction force in ER fluids increases with the applied electric field according to a quadratic law ∝ 0 2 . [3][4][5] However, lower exponents (1≤n<2) in the dependence of Felec on E0 were observed experimentally at a high applied electric field. 6,7 This deviation from the quadratic law was interpreted theoretically by considering, in addition to the solid particle conductivity, the dependence of the matrix conductivity on the electric field which gives rise to a saturation of the local electric field.…”
Section: Introductionmentioning
confidence: 96%
“…These studies showed that the attraction force in ER uids increases with the applied electric eld according to a quadratic law F elec f E 0 2 . [3][4][5] However, lower exponents (1 # n <…”
Section: Introductionmentioning
confidence: 99%
“…Especially for micro-(or nano-) flow devices, stable flow within the gap significantly narrower than several hundred micrometers should also be required [21]. Therefore, particular attention has been directed toward the ER nano-suspension based on nano-particles [22,23].…”
Section: Introductionmentioning
confidence: 99%